KONSTRUKSI HUKUM PENCALONAN PRESIDEN DAN WAKIL PRESIDEN YANG MENCERMINKAN DEMOKRASI PANCASILA BERDASARKAN UU NOMOR 7 TAHUN 2017 - Muhammad Randy Effendi; Ismail; harta (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
This study aims to examine and determine the Legal Construction of Presidential and Vice Presidential Nominations that reflect Pancasila democracy in relation to the provisions of Law Number 7 of 2017 concerning General Elections. The formulation of the problem that the author poses is, What is the Ideal Legal Construction of Presidential and Vice Presidential Nominations to Realize Pancasila Democracy? The research method used is normative where the data used is secondary data in the form of legal materials. In addition to using secondary legal materials, this study also uses several theories to dissect the problems in this study. The results of the study obtained are that the nomination of the president and vice president is regulated in Article 6A paragraph (2) of the Constitution of the Republic of Indonesia, namely "The presidential and vice presidential candidate pairs are proposed by political parties or a coalition of political parties participating in the general election before the general election is held". Regulations regarding the mechanism for nominating the presidential and vice presidential positions are stated in Law Number 7 of 2017 concerning General Elections, Article 222 regulates the same thing regarding filling the presidential and vice presidential positions. The presidential threshold has violated political rights, including the right to be elected and to elect the people protected by the constitution. This restriction on alternative candidates certainly means limiting the people’s political channels and to a certain extent can result in an increase in the number of abstainers or white groups in the election. In addition, the opportunity for the people to be elected as candidates is also limited because not all political parties participating in the election have the right to nominate presidential and vice presidential candidate pairs because they are constrained by the Presidential Threshold requirements. The policy of direct presidential elections within the framework of simultaneous elections is still problematic. The existence of a threshold for political parties to have the right to nominate presidential and vice presidential candidate pairs (Presidential Threshold) in the General Election held simultaneously, has legal implications, namely violating the 1945 Constitution concerning the Presidential System, contrary to Article 6A paragraph (2) of the 1945 Constitution.